TRAINING ON ENTREPRENEURSHIP SKILLS IMPROVEMENT WITH BUSINESS MODEL CANVAS (BMC) IMPLEMENTATION FOR STUDENTS OF SMA NUSANTARA BALIKPAPAN - Ivani, Kartika Aprilia; Hestiningtyas, Annisa; Ahmad, Ahmad; Pratama, Aditya; Salamsjah, Salamsjah (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Entrepreneurship skills are essential competencies for the younger generation to face future job market challenges. This activity aims to enhance the entrepreneurship skills of SMA Nusantara Balikpapan students through training using the Business Model Canvas (BMC) approach. The training method encompasses five main stages: pretest, material provision, training, discussion, and post-test. Initially, the pretest measures the students' initial knowledge and entrepreneurship skills. Subsequently, materials on the basic concepts of entrepreneurship and BMC were provided as a theoretical foundation. Intensive training focused on applying BMC in designing business models. Discussions, encouraged collaboration and idea sharing among students. In the final stage, a post-test evaluated the improvement in students' skills and understanding after the training. The results indicated a significant increase in students' entrepreneurial knowledge and skills following the training. Data from the pretest and post-test were analyzed using descriptive and inferential statistics, confirming the training's effectiveness with BMC implementation. Additionally, students showed increased motivation and interest in developing their business ideas. In conclusion, entrepreneurship training with the BMC approach effectively enhances the skills and understanding of SMA Nusantara Balikpapan students. This program is expected to be adopted by other schools to prepare students for the workforce and foster a generation that is creative, innovative, and ready for entrepreneurship.